2009
DOI: 10.14411/eje.2009.071
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a predatory ladybird beetle, Anegleis cardoni (Coleoptera: Coccinellidae) on three aphid species

Abstract: Abstract. Qualitative and quantitative differences in prey are known to affect the life histories of predators. A laboratory study was used to evaluate the suitability of three aphid prey, Aphis gossypii, Aphis craccivora and Lipaphis erysimi, for the ladybird beetle, Anegleis cardoni (Weise). Development was fastest on A. gossypii followed by A. craccivora and L. erysimi. Percentage pupation, immature survival, adult weight and the growth index were all highest when reared on A. gossypii and lowest on L. erys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 49 publications
4
19
0
1
Order By: Relevance
“…Semyanov, 2001;Pervez and Omkar, 2004;Nasution, 2007), prey quality (e.g. Kalaskar and Evans, 2001;Omkar and Srivastava, 2003;Kalushkov and Hodek, 2004;Michaud, 2005;Omkar and Mishra, 2005), prey quantity (Omkar and Pervez, 2003;Omkar et al, 2009), photoperiods and wavelengths (Hodek and Ružička, 1979;Hodek and Iperti, 1983;Mishra and Omkar, 2005;Omkar et al, 2005) and sex (Hodek and Hönek, 1996;Dixon, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Semyanov, 2001;Pervez and Omkar, 2004;Nasution, 2007), prey quality (e.g. Kalaskar and Evans, 2001;Omkar and Srivastava, 2003;Kalushkov and Hodek, 2004;Michaud, 2005;Omkar and Mishra, 2005), prey quantity (Omkar and Pervez, 2003;Omkar et al, 2009), photoperiods and wavelengths (Hodek and Ružička, 1979;Hodek and Iperti, 1983;Mishra and Omkar, 2005;Omkar et al, 2005) and sex (Hodek and Hönek, 1996;Dixon, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mustard aphid, L. erysimi has higher levels of proteins (Atwal and Sethi, 1963), but numerous studies have reported that this aphid sequesters chemicals from its host plant, which contains certain alkaloids that are toxic for many ladybirds (Hodek, 1956;Okamoto, 1966). Its pungent smell, possibly due to the presence of allyl isothiocyanates, is also responsible for its reduced suitability as a prey (Joshi et al, 1999;Noble et al, 2002;Omkar et al, 2009). Studies have further shown that the allelochemicals that L. erysimi derive from their host plant are highly suitable for the metabolic activity of C. septempunctata while C. transversalis cannot easily detoxify the harmful chemicals of L. erysimi; hence the former and latter have higher and lower predation rates on this aphid prey, respectively (Kumar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Saboori, Hosseini, and Hatami (2003) observed that the predator mite Allothrombium pulvinum Ewing selected eggs of P. citri according to prey quality and larger size over Pulvinaria aurantii Cockerell eggs. Moreover, Omkar, Kumar, and Sahu (2009) reported that the fecundity and survival rate of Anegleis cardoni Weise were higher when they were reared on Aphis gossypii Glover than Aphis craccivora Koch and Lipaphis erysimi Kaltenbach, respectively.…”
Section: Discussionmentioning
confidence: 99%